2022
DOI: 10.1002/pts.2648
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric oxygen indicator films based on β‐cyclodextrin grafted chitosan/montmorillonite with redox system for intelligent food packaging

Abstract: Oxygen is an important factor in food deterioration; thus, packaging, with an in-built oxygen indicator, has been widely developed. Here, a safer, natural product-based, colorimetric oxygen indicator film based on β-cyclodextrin grafted chitosan/montmorillonite with methylene blue/glucose system was fabricated.Methylene blue in the activated films was reduced to leuco-form (colourless) by glucose and reverted to blue with oxygen exposure. Glucose, as well as the reducing agent for methylene blue, crosslinked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…PET films may also delay the color change to blue with a low oxygen permeability. In addition, the film can elongate the storage time for three weeks in a refrigerator [ 106 ]. When MMT–copper oxide nanocomposites (MMT-CuO) were incorporated into the chitosan matrix, it improved the optical, mechanical, and antibacterial properties.…”
Section: Chitosan Compositesmentioning
confidence: 99%
“…PET films may also delay the color change to blue with a low oxygen permeability. In addition, the film can elongate the storage time for three weeks in a refrigerator [ 106 ]. When MMT–copper oxide nanocomposites (MMT-CuO) were incorporated into the chitosan matrix, it improved the optical, mechanical, and antibacterial properties.…”
Section: Chitosan Compositesmentioning
confidence: 99%
“…Recent studies have started looking into developing safer products such as edible pH sensor 52 and natural product-based oxygen indicators. 53 However, studies conducted by Aday and Yener, 54 and O'Callaghan and Kerry 55 found that from a consumer point of view, the perceived risk of being misled with innovative packaging claims was still a barrier to adoption. Consumers may be more willing to accept a technology after viewing educational commercials.…”
Section: Consumers' Drivers and Barriers Of Intelligent Packagingmentioning
confidence: 99%
“…In addition, consumers may perceive a risk that indicators could leak substances onto food, cease contact with food (decreasing reliability) or be manipulated by retailers. Recent studies have started looking into developing safer products such as edible pH sensor 52 and natural product‐based oxygen indicators 53 . However, studies conducted by Aday and Yener, 54 and O'Callaghan and Kerry 55 found that from a consumer point of view, the perceived risk of being misled with innovative packaging claims was still a barrier to adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue was reduced to its colorless form by glucose and turned blue on exposure to oxygen. Films based on these polymers demonstrated storage stability at low temperatures, which makes them an excellent option for cold-stored food products due to their effectiveness as colorimetric oxygen indicators [137].…”
Section: Gas Indicatorsmentioning
confidence: 99%